2015
DOI: 10.1002/lsm.22291
|View full text |Cite
|
Sign up to set email alerts
|

The time factor in the LDI (Laser Doppler Imaging) diagnosis of burns

Abstract: LDI is a useful method for wound healing prediction and an indication of the necessity of surgery. We have demonstrated that the diagnosis of the healing capacity of LDI needs to take into account the factor of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It is well documented in human studies that the reliability of LDI scanning in the immediate (early) post-burn period is questionable [ 51 , 52 ]. Studies by Stetinsky et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented in human studies that the reliability of LDI scanning in the immediate (early) post-burn period is questionable [ 51 , 52 ]. Studies by Stetinsky et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Stetinsky et al . [ 51 ] report that the perfusion status of both superficial partial thickness and deep partial thickness burns were similarly low in the acute post-burn period (48 hours). They suggested that localised oedema may compress the vascular supply to the area and thus low perfusion reflects disruption rather than actual destruction of the microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Hoeksema et al measured the perfusion on different days after injury, [8] and found that the best interval to assess the depth using this method is between 3 and 5 days. Štětinský et al found that outcome could not be predicted accurately by LDI until the 3 rd day [9].…”
Section: Discussionmentioning
confidence: 99%
“…Stetinsky et al demonstrated that duration between burn injury and scan should be used to determine cut-off perfusion scores for decision to operate. This is due to the dynamic nature of burn wounds, and linear healing that occurs with time [20]. We scanned patients at an average of 2.68 days post burn injury, as early excision and closure of deep wounds has been associated with reduced morbidity and mortality [21,22].…”
Section: Colour Pallet Perfusion Unitsmentioning
confidence: 99%